Improving nature-based tourism accounts : The importance of national data for robust ecosystem service estimates - Jussila, Tytti; Hurskainen, Pekka; Neuvonen, Marjo; Artell, Janne; Laalo, Marianne; Saikkonen, Liisa (Pensoft Publishers, 2026)
The new EU regulation on ecosystem accounting requires Member States to report annually on the supply and use of seven ecosystem services. To support this process, Eurostat provides a voluntary INCA tool along with default datasets and methods. While these resources enable basic compliance with the reporting requirements, the top-down, centrally provided input data and assumptions are generic, not fully comprehensive and may lack accuracy in many national contexts. Integration of national data and context-specific assumptions is, therefore, recommended to improve reliability and national relevance of accounts. In this study, we assessed how input data choices affect nature-based tourism accounts in Finland. We compiled two sets of accounts with the INCA tool: one using the default dataset and one with nationally sourced input data. Improvements in the nationally adjusted dataset include high-resolution travel statistics, spatial information on accommodation locations and adjusted proxies for recreational attractiveness. The comparison of resulting accounts revealed substantial differences: the default approach underestimated domestic nature-based tourism volumes – mainly due to missing non-commercial accommodation use – and produced unrealistic spatial patterns that overlooked several key destinations. National data provided markedly higher and more plausible estimates, with a broader and more accurate distribution across the landscape and a shift in ecosystem-level supply from forest-dominated to a more balanced contribution of lakes, marine areas and other ecosystems. Our findings demonstrate that using more comprehensive inputs, with higher spatial accuracy and closer alignment with national realities, can substantially change the magnitude and spatial distribution of estimated ecosystem service supply. Incorporating national expertise and datasets is essential to go beyond minimum compliance and to produce ecosystem accounts that are robust enough to support informed policy-making.
Keywords: ecosystem accounting; recreation potential; spatial modelling; cultural ecosystem services